2000
DOI: 10.1161/01.atv.20.7.1796
|View full text |Cite
|
Sign up to set email alerts
|

Increased Production of HDL ApoA-I in Homozygous Familial Defective ApoB-100

Abstract: Abstract-Familial defective apolipoprotein (apo) B-100 (FDB) is a frequent cause of hypercholesterolemia. Hypercholesterolemia in homozygous FDB is less severe than in homozygotes for familial hypercholesterolemia. Recently, we showed decreased low density lipoprotein (LDL) apoB-100 fractional catabolism and decreased production of LDL due to an enhanced removal of apoE-containing precursors in a patient with homozygous FDB. The effects of defective apoB-100 on high density lipoprotein (HDL) metabolism are unk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…Interestingly, HDL production rate is not significantly altered in heterozygotes, which may reflect a compensatory HDL synthesis rate due to the remaining partial LDLR activity and consequently remaining cell membrane receptor-mediated lipoprotein flux. This observation on lipoprotein flux in the presence of LDLR is confirmed by increased production of HDL apoA-I in a homozygous apoB defective subject [Schaefer et al, 2000]. This flux is apoE mediated, since apoB is defective.…”
Section: Ldl Receptor Deficiencysupporting
confidence: 52%
“…Interestingly, HDL production rate is not significantly altered in heterozygotes, which may reflect a compensatory HDL synthesis rate due to the remaining partial LDLR activity and consequently remaining cell membrane receptor-mediated lipoprotein flux. This observation on lipoprotein flux in the presence of LDLR is confirmed by increased production of HDL apoA-I in a homozygous apoB defective subject [Schaefer et al, 2000]. This flux is apoE mediated, since apoB is defective.…”
Section: Ldl Receptor Deficiencysupporting
confidence: 52%
“…The importance of regular exercise in preventing and treating chronic disease is generally accepted (25). The main findings of the present study were increase in lymphocyte ABCA1protein expression, plasma HDL-C, Apo-I and a reduction in plasma LDL-C concentrations following eight-week interval endurance rope training.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in plasma and tissue adiponectin concentrations and expression following an exercise training program was considered to be an effective factor to regulate ABCA1 expression (31, 32). It is shown that cAMP can also be enhanced ABCA1 gene transcription (25). In the current study there were increase in concentrations of ApoA-I and HDL-C and decrease in LDL-c value following IERT program but the changes weren’t significant, these results are consistent with the results of some studies (18, 33-36) contrast with some others (27, 35).…”
Section: Discussionmentioning
confidence: 99%
“…Nanjee et al (24) have found particles resembling pre␤ 1 -HDL in the leg lymph, suggesting that it was formed extrahepatically. The rate of apoA-I synthesis in humans has been estimated to be about 700 mg/day (25,26). Thus, if pre␤ 1 -HDL is the sole precursor of HDL, and one leg represents about one-third of the total body muscle mass, then it follows that there is substantial recycling of apoA-I between nascent and mature HDL particles.…”
Section: Discussionmentioning
confidence: 99%